Human Finitude and Historical Materialism (World Marxist Review, 2025)
In his latest book, The Culmination: Heidegger, German Idealism, and the Fate of Philosophy, Robert Pippin reads Heidegger’s critique of German idealism as an effort to re-ground philosophical thought in the thinking of finite, mortal, concretely situated, embodied human beings. Pippin’s argument reminds one of another critique of German idealism: Marx’s. While Pippin acknowledges that Marx and the materialist tradition suggested another way out of the self-enclosed rationalism of idealism, he ultimately supports Heidegger’s hermeneutic solution. I will argue that historical materialism is a more complete and coherent alternative to idealism than Heidegger’s existential phenomenology. Despite the fact that it prioritises concrete social and historical research, it is not an anti-philosophical empirical research program but implies a new way of understanding core philosophical problems. I will contend this this new, historical and materialist way of doing philosophy is a more coherent articulation of the dispositions and fundamental concerns of finite human beings. The historical materialist conception of human finitude exposes Heidegger’s understanding of human finitude as one-sided and abstract.